Emotional face processing in post-traumatic stress disorder after reconsolidation impairment using propranolol: A pilot fMRI study. (December 2015) - Mahabir, Megan; Tucholka, Alan; Shin, Lisa M.; Etienne, Pierre; Brunet, Alain
Highlights: We examined neural responses to threat after impaired reconsolidation in PTSD. Traumatic memory reconsolidation impairment via propranolol decreased PTSD severity. ACC activity to fearful cues was greater after vs. before impaired reconsolidation. Abstract: Individuals with post-traumatic stress disorder (PTSD) exhibit exaggerated emotional reactions to threatening stimuli, which may represent deregulated fear-conditioning, associated with long-term adaptations in the sympathetic nervous system. Within a repeated measures design, functional magnetic resonance imaging (fMRI) was employed to investigate neural responses to threat in PTSD participants (N = 7), during the presentation of emotional facial expressions. Scans were separated by 6 weekly reconsolidation impairment treatment sessions, consisting of traumatic memory reactivation under the influence of propranolol. Greater activation before versus after treatment emerged in the thalamus and amygdala during fearful versus neutral face processing. Furthermore, participants showed greater activation after versus before treatment in the right anterior cingulate, during fearful relative to happy face processing. PTSD symptoms significantly improved ( d = 1.75), post-treatment. These preliminary results suggest that aberrant emotional responding is modulated by noradrenergic plasticity within the amygdala-prefrontal cortex circuit, a neural substrate for the pharmacological treatment of PTSD.